Изменение некоторых морфологических признаков в онтогенезе у калянуса гельголандского — Calanus helgolandicus Claus (Crustacea, Copepoda) - Ковалев, А.В. (Вестник зоологии, 1969)
Changes of some morphological characters (form of the body sizes of different characters) during the ontogeny in Calanus helgolandicus are shown to favour the increase in their rate of movement. The analysis of morphometric data in the copepod stages of C. helgolandicus enabled sexual dimorphism of the species to be detected at the fourth copepod stage.